KOMPETENSI PENYULUH PERTANIAN LAPANGAN DALAM USAHATANI TANAMAN JAGUNG DI DESA KASAKA KECAMATAN KABAWO KABUPATEN MUNA - Ege Hermadan; Sukmawati Abdullah; Putu Arimbawa (Department of Agricultural Extension, Faculty of Agriculture, Halu Oleo University, 2024)
The maize crop production in Kabawo Sub-district, Muna Regency has decreased. It is suspected that the competence of agricultural extension workers is one of the factors that has a relationship with the decline in production. The purpose of the study was to determine the level of competence of field agricultural extension workers in Kasaka Village, Kabawo District, Muna Regency. The population of the study consisted of all corn farmers in Kasaka Village who received assistance from field agricultural extension officers in farming. This amounted to 78 farmers. A total of 15% of the population was selected as the research sample, which was determined to be 20 corn farmers using the sloving method. Sampling was conducted using a random sampling method. Data collection techniques included observation, interviews, and documentation, utilizing research media in the form of questionnaires. The data were analyzed using quantitative descriptive analysis, employing the class interval formula to assess the level of competence of field agricultural extension workers in maize farming. The results indicated that the competence of field agricultural extension workers in corn farming in Kasaka Village, Kabawo Sub-district, Muna Regency is generally in the medium category. This can be observed in the technical competence, managerial competence, and communication competence of field agricultural extension workers, which are still moderate. Technical competence describes the ability of extension workers to apply various types of crop cultivation knowledge. It encompasses the ability to apply theoretical knowledge to practical situations and to adapt to changing circumstances. Managerial competence describes the ability of extension workers to organize and manage all forms of resources owned by both themselves and their targets. It encompasses the ability to plan, organize, and coordinate activities and resources effectively and efficiently. Communication competence describes the ability of extension workers to communicate and convey information that can be easily understood by the farmers themselves. It encompasses the ability to communicate effectively and efficiently, using appropriate language and terminology, and to convey information in a clear and concise manner.